Bilateral Malrotation and a Congenital Pelvic Kidney with Varied Vasculature and Altered Hilar Anatomy - J. Singh; N. Singh; K. Kapoor; M. Sharma (Case Reports in Medicine)
Variations of structure and position of the kidney along with variations of renal vessels are most frequently reported. Rotational variations form a rare entity that are not cited in most embryology textbooks. During an educational cadaveric dissection of a 42-year-old male, a complex picture of bilateral anatomical variants was encountered. Malrotation of both kidneys and a left lobulated ectopic kidney along with open hilum was observed. The left kidney showed a pelvic position in front of sacral promontory with three renal arteries retaining its embryological aortoiliac branches and two renal veins draining into right common iliac vein. These variations have an embryological base. Pelvic kidney with rotational variation though comparatively rare assumes great importance in view of present-day surgical procedures like laparoscopic radical nephrectomy, percutaneous nephrectomy, and renal transplantation.